Pengaruh Self-Regulation Terhadap Motivasi Berprestasi Pada Siswa Kelas V SD - Pramita, Putu Ayu; Suarni, Ni Ketut; Margunayasa, I Gede (Attadib: Journal of Elementary Education, 2024)
Self-Regulated Learning or Independent Learning is a learning strategy that is currently being discussed a lot in the world of education. Educational practitioners have widely researched SRL. One of them is the relationship between SRL and student achievement motivation. This research is qualitative research with a literature review approach. This research aims to determine the effect of SRL on the achievement motivation of fifth-grade elementary school students. The research was conducted using the observation method on the achievement motivation of fifth-grade elementary school students. The research results show that using SRL as a classroom learning method can help students grow their achievement motivation. This research shows that SRL and achievement motivation have a positive relationship. In the future, research on SRL can be developed by exploring other academic potentials that can be improved besides student achievement motivationTRANSLATE with x EnglishArabicHebrewPolishBulgarianHindiPortugueseCatalanHmong DawRomanianChinese SimplifiedHungarianRussianChinese TraditionalIndonesianSlovakCzechItalianSlovenianDanishJapaneseSpanishDutchKlingonSwedishEnglishKoreanThaiEstonianLatvianTurkishFinnishLithuanianUkrainianFrenchMalayUrduGermanMalteseVietnameseGreekNorwegianWelshHaitian CreolePersian //  TRANSLATE with COPY THE URL BELOW Back EMBED THE SNIPPET BELOW IN YOUR SITE Enable collaborative features and customize widget: Bing Webmaster PortalBack//